Conceito de trabalho análogo ao de escravo no Brasil: limites normativos à adoção de um conceito restrito - Saldanha, Milton Nogueira da Cruz (2018)
The object of the present dissertation is the concept of work analogous to slave labor in Brazil and the normative limits for its speculative reduction. The objective is to analyze the concept of work analogous to slavery, aiming at its adequacy with the Federal Constitution of 1988, with the international normative diplomas of which Brazil is a signatory and contemplating current forms of exploitation of human labor, resulting from the constant transformations of the contemporary world. For that, the historical antecedents of slave labor were described; it was characterized the work in conditions analogous to slavery in international and national regulations, as well as discussed the influence of the application of the concept of labor under conditions analogous to slave labor in the respective eradication, in the light of fundamental rights. The work was developed through a bibliographical and documentary research, involving national and international documents on the subject. The conclusion was that the concept of work developed under conditions analogous to slave labor should encompass all the variables implicit in this practice, either in its older forms or in the new models, in addition to being in consonance with the 1988 Constitution, with international norms and, mainly, to include all the ways in which slave labor is exploited.